Textbook of english class 10 - Niazi awais amara (Peshawar National book foundation, 2025)
The Class 10 English textbook is designed to develop students$1 (Blanguage skills, critical thinking, and appreciation of literature. It usually contains a balanced mix of prose, poetry, and plays, along with grammar and writing practice. The prose lessons introduce students to thought-provoking stories, essays, and real-life accounts that broaden their worldview and moral understanding. The poetry section nurtures imagination and emotional sensitivity through classic and modern poems. Drama provides exposure to dialogue, character, and stagecraft. In addition, the textbook emphasizes reading comprehension, vocabulary building, and writing skills such as essays, letters, reports, and applications. Altogether, the book aims to improve communication skills, foster creativity, and prepare students for higher studies and practical life.s